2010
DOI: 10.1158/0008-5472.can-10-1949
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling in Progressive Stages of Fumarate-Hydratase Deficiency: The Contribution of Metabolic Changes to Tumorigenesis

Abstract: Hereditary leiomyomatosis and renal cell carcinoma (HLRCC) is caused by mutations in the Krebs cycle enzyme fumarate hydratase (FH). It has been proposed that "pseudohypoxic" stabilization of hypoxiainducible factor-α (HIF-α) by fumarate accumulation contributes to tumorigenesis in HLRCC. We hypothesized that an additional direct consequence of FH deficiency is the establishment of a biosynthetic milieu. To investigate this hypothesis, we isolated primary mouse embryonic fibroblast (MEF) lines from Fh1-deficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 51 publications
5
44
0
2
Order By: Relevance
“…These results imply that decreased FH expression might contribute to tumorigenesis in RCC by promoting the expression of hypoxia-induced genes and cell proliferation, rather than by acting on aspects of the aggressive phenotype such as progression and invasion. In support of the present findings, Ashrafian et al [28] suggested that FH deficiency compels cells to adapt to an early, reversible, and progressive pro-tumorigenic metabolic environment characterized by the increased expression of HIF-1α target genes and glycolytic or biosynthetic gene expression changes. These authors concluded that these metabolic and gene expression changes seemed to be sufficient to promote cellular growth and proliferation, and subsequent expression changes putatively arising from genetic and epigenetic changes within preneoplastic cells might drive tumorigenesis.…”
Section: Discussionsupporting
confidence: 88%
“…These results imply that decreased FH expression might contribute to tumorigenesis in RCC by promoting the expression of hypoxia-induced genes and cell proliferation, rather than by acting on aspects of the aggressive phenotype such as progression and invasion. In support of the present findings, Ashrafian et al [28] suggested that FH deficiency compels cells to adapt to an early, reversible, and progressive pro-tumorigenic metabolic environment characterized by the increased expression of HIF-1α target genes and glycolytic or biosynthetic gene expression changes. These authors concluded that these metabolic and gene expression changes seemed to be sufficient to promote cellular growth and proliferation, and subsequent expression changes putatively arising from genetic and epigenetic changes within preneoplastic cells might drive tumorigenesis.…”
Section: Discussionsupporting
confidence: 88%
“…GSE26574 and GSE20896) (3,15). Concordant with our cell culture models, HLRCC tumors showed significantly increased expression levels of FTL, FTH1, and FOXM1 as well as the FOXM1 target genes AURKA, AURKB, and CDK1 compared to those in normal kidney tissues (Fig.…”
Section: Resultssupporting
confidence: 76%
“…This view is supported by the existing literature. For example, it was recently reported that mice exposed to 3 weeks of normobaric hypoxia had reduced complex II, complex IV, and aconitase activity in cardiac mitochondria 35 while fumarate accumulation leads to pseudohypoxic activation of hypoxiainducible factor-1α, 36 suggesting that many of the same reactions highlighted here indeed have important roles in hypoxic adaptation and, hence, survival. Our combined approach also yielded an unexpected benefit: Computational analysis was able to provide suggestions as to whether genes were under positive or negative selective pressure (an important distinction to which traditional genome-wide analytic techniques are blind).…”
Section: Downloaded Frommentioning
confidence: 77%